Corporate social responsibility, public relations & community development : emerging perspectives from Southeast Asia - Sison, Marianne D.; Panol, Zeny Sarabia- (New York : Routledge, 2019)
"Diverse in economic development, political and mass media systems, the countries in South East Asia cast a unique light on the parallels between development-cum-participative communication and corporate social responsibility. In our globalized environments, knowledge of power, culture and the colonial histories that influence and shape business and governance practices are increasingly important. Focusing on six countries--Indonesia, Malaysia, the Philippines, Singapore, Thailand and Vietnam-- the book discusses how PR and CSR discourse are constructed, interpreted, communicated and enacted in this diverse emerging region. By connecting the disparate disciplines of participatory and development communication with public relations and corporate social responsibility discourse, this innovative text explores the tensions between concepts of modernity and traditional values and their role in engendering creativity, compliance or resistance"--
Introduction : exploring the connections -- Beyond nation building: CSR and sustainability in Indonesia -- CSR/PR discourse as advocacy and aspirational talk in Malaysia -- CSR as social development in postcolonial Philippines -- Singapore's strategic social enterprise and inclusive communication -- Sustainable community development and risk mitigation in Thailand -- Blurring CSR/PR boundaries : transactional approaches in Vietnam -- Conclusion : connecting the narratives.
Includes bibliographical references and index.
Keywords: Social responsibility of business -- Southeast Asia; Public relations -- Southeast Asia; Community development -- Southeast Asia; Print books